The anterior hanging-approach improves postoperative course after right hepatectomy in patients with colorectal liver metastases. Results of a prospective study with propensity-score matching comparison. Issue 2 (February 2016) - Llado, L.; Muñoz, A.; Ramos, E.; Torras, J.; Fabregat, J.; Rafecas, A.
Abstract: Purpose: To establish the role of the anterior approach with liver hanging maneuver for right hepatectomy in patients with colorectal liver metastases (CRLM). Summary background data: The indications for hepatectomy in patients with CRLM are expanding. The liver remnant must be protected to avoid morbidity. Methods: We prospectively enrolled all patients with the diagnosis of CRLM requiring right hepatectomy from 2009 to 2012. In all cases right hepatectomy with an anterior-hanging maneuver approach was attempted. We compared the group of patients who underwent this procedure with a group of patients who had previously undergone a conventional right hepatectomy. To minimize selection bias, propensity score matching was performed, based on baseline patient characteristics. Results: A right hepatectomy was planned in 57 cases. The anterior-hanging approach was feasible in 85% of cases. Overall morbidity was similar. In-hospital mortality due to hepatic insufficiency was 2.3% in anterior-hanging group compared to 9% in the conventional group (p = 0.30). The incidence of ascites was significantly greater in the conventional group (AH: 18% vs Conv: 54%; p = 0.002), and hospital stay was longer (AH: 10.9 ± 5.7 vs Conv: 14.4 ± 8.1 days; p = 0.05). Bilirubin levels were significantly lower in anterior-hanging group in day 1 and 3. There were no differences on recurrence nor survival. Conclusions: The anterior-hanging approach for right hepatectomy in patients with CRLM can be used safely with a high feasibility rate. Its use contributes to improve postoperative course.